Simbolisme dan Makna dalam Syair 'Atas Pisang' pada Tari Dolalak: Pendekatan Semiotika Barthes - Maria Magdalena Cita Hapsari; Adhitya Darmantho; Malarsih Malarsih; Syahrul Syah Sinaga (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Among the many verses used in the Dolalak Dance, the verse "Atas Pisang" holds a unique position. This verse is often recited at the end of the performance, signifying a solemn and message-laden conclusion. This study aims to examine the symbolism and meaning within the ‘Atas Pisang’ verse in the Dolalak Dance. This research is a qualitative interpretive study employing Roland Barthes' semiotic approach regarding denotation and connotation meanings. The findings indicate that the ‘Atas Pisang’ verse in the Dolalak Dance, through its symbolism and metaphors, conveys various relevant and wise life advice. The balance between visible outcomes and underlying essence, hope and recovery from difficulties, the importance of actions in pursuing desires, appreciation of the past and experiences, and wisdom in family relationships are the main messages conveyed. The ‘Atas Pisang’ verse teaches that a balanced life, filled with hope, active pursuits, appreciation of the past, and wisdom in family relationships are keys to achieving a harmonious and meaningful life.